The Effect of Earnings Persistence, Systematic Risk, and Conservatism on Earnings Informativeness - Noviola Suhandi; Paulina Sutrisno (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to examine several factors that are predicted to affect earnings informativeness. This study examines several independent variables, namely earnings persistence, company growth, systematic risk, capital structure, profitability, and conservatism on earnings informativeness. The research sample was selected based on certain criteria with a total of 43 manufacturing companies on the Indonesia Stock Exchange for the period 2017 to 2019. The research data was tested using a statistical technique, namely multiple linear regression. The results of this study indicate that company growth has a negative effect on earnings informativeness. On the other hand, earnings persistence, systematic risk, capital structure, profitability, and conservatism have no effect on earnings informativeness.